2018
DOI: 10.15406/ijfcm.2018.02.00056
|View full text |Cite
|
Sign up to set email alerts
|

Contextual treatment: a conceptualization and systematization from general medicine

Abstract: Family doctors do not treat illnesses but rather care for people in their contexts. And so, an important characteristic of family medicine is that you cannot separate the individual from its context, or the physical from the psychic. General / family medicine is context-oriented. Illness is a relational concept. It is related to contexts; appears between the person and their relationships with the contexts; it does not exist isolated from the contexts. The real object of the work of general practitioner is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…It has been reported that this therapeutic context induces biomedical processes in the patient's brain that may enhance or reduce the effects of chosen interventions. The context thus works as a drug, with real effects and side effects [7], and we must remember that, the nocebo-placebo effect is also included here [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that this therapeutic context induces biomedical processes in the patient's brain that may enhance or reduce the effects of chosen interventions. The context thus works as a drug, with real effects and side effects [7], and we must remember that, the nocebo-placebo effect is also included here [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the family and the context must be taken into account as essential elements for the treatment (hygienic measures, diets, taking drugs, exercise or rest, etc.) (17,(28)(29)(30)(31)(32).…”
Section: General Systems Theory and General Medicinementioning
confidence: 99%
“…Here, general practitioner works by occupying the interstices of daily life, and he uses a series of specific tools specific to the specialty of general medicine to work from these "interstices" between biological, psychological and social structures [30]. Table 2 presents a conceptual approach to systematization of these tools and technologies [19,20,22,[31][32][33][34][35][36][37][38][39].…”
Section: The Concepts Of the Theoretical Framework Of Family Medicinementioning
confidence: 99%